Efficacy of lacosamide add-on therapy on Refractory Focal Epilepsies in children and adolescents: An open-label clinical trial - Tayebeh Mohammadi; Jafar Nasiri; Mohammad Reza Ghazavi; Omid Yaghini; Neda Hoseini (Wolters Kluwer Medknow Publications, 2022)
Objective: Epilepsy is a chronic neurological disorder that affects 0.5%-1% of children. 30%-40% of patients are resistant to current anti-epileptic drugs. Lacosamide (LCM) appeared to be effective, safe, and well tolerated in children and adolescents. This study was aimed to evaluate whether LCM could be an effective add-on therapy in children with refractory focal epilepsies. Methods: This study was conducted from April 2020 to April 2021 in Imam Hossein Children Hospital, Isfahan, Iran. We included 44 children aged 6 months to 16 years with refractory focal epilepsy (based on International League Against Epilepsy criteria). LCM was given in divided doses of 2 mg/kg/day, increasing by 2 mg/kg every week. The first follow-up visit was 6 weeks later, when all patients had reached the therapeutic dose. Findings: The average age of the patients was 89.9 months. 72.5% of children had focal motor seizures. Evaluation of percent change in seizure frequency and duration before and after treatment showed a 53.22% reduction in seizure frequency and 43.72% reduction in seizure duration after treatment. Our study group tolerated LCM well, with few side effects. Headache, dizziness, and nausea were common side effects. In line with other studies, none of the suspected risk factors could predict response to LCM treatment. Conclusion: LCM appears to be an effective, safe, and well-tolerated medication in children with uncontrolled drug-resistant focal epilepsy.